(untitled) (Fiep Bulletin - online, 2014)
The present work is an adaptation of my graduation paper, composed from qualitative research and case studies that have as subjects: Physical Education and Autism. The objective is to identify the paths that the teacher of Physical Education can follow to extend the motor repertoire of the pupils diagnosed with autism, contributing with professionals and families of these people interested in understanding the behaviors presented by them, as well as searching better strategies to teach them. Such research procedure becomes relevant due to the importance of this subject and to the lack of available literature on this topic in Brazil. The lessons occurred individually. The study had the duration of sex months, from June to January of 2006. The lessons had been given to two children diagnosed with autism, being both of the masculine sex and in the age group of 3 and 5 year old. The lessons were given in the town of Barra do Piraí (Rio de Janeiro State), in a house adapted for this purpose. With the frequency of two trice a week. This work is based on disciplines such as Physical Education for Special Carriers of Necessities, Psychology and Sport Training. The project was developed by the teacher Daniel Laureano Candido and guided by MSc. Sérgio Eduardo Santos de Moura. The mentioned work has as its methodology the analysis of the applied behavior, since the symptoms of the autism are basically behavioral. We try to understand the reason of certain behaviors and relate them to praxis of the Physical Education. Each stage of the lesson was registered in charts with a punctuation that goes from 1 to 10, created by the MSc. Sandro Arêdes and by the author and has as an evaluation criterion motor, visual and behavioral aspects.